The High-Performance Linpack (HPL) Evaluation on MIHIR High Performance Computing Facility at NCMRWF - Gangwar, Shivali; Athiyaman, B; D, Preveen Kumar (International Journal of Computer Sciences and Engineering, 2025)
The National Centre for Medium Range and Weather Forecasting (NCMRWF) has, the MIHIR High Performance Computing (HPC) Facility with total computing capacity of 2.8 Petaflops to run Numerical Weather Prediction (NWP) models, enabling accurate and timely weather forecasting. These models need computations performed in PFLOPS (Peta Floating Point Operations Per Second). The HPC nodes are interconnected by the high speed, low latency Cray Aries network. High Performance Linpack (HPL) version 2.3 has been compiled and installed on the system for the study. The purpose of running HPL is to demonstrate the current computing performance of the HPC, and to assess the systems efficiency by analyzing the actual calculated performance (Rmax) and the theoretical peak performance (Rpeak, derived from system specifications). We present a performance evaluation of the HPL benchmark on MIHIR, conducting a detailed analysis of HPL parameters to optimize performance. The aim is to identify the best-optimized parameter values for MIHIR and determine the maximum achievable performance of the compute nodes, utilizing up to 300 nodes available for research.